Efficacy and Safety of Mepolizumab (Anti-Interleukin-5) Treatment in Gleich’s Syndrome - Matucci, Andrea; Liotta, Francesco; Vivarelli, Emanuele; Dies, Laura; Annunziato, Francesco; Piccinni, Marie Pierre; Nencini, Francesca; Pratesi, Sara; Maggi, Enrico; Vultaggio, Alessandra (Frontiers in Immunology, 2018)
Gleich’s syndrome (GS) is characterized by recurrent episodes of angioedema, increase in body weight, fever, hypereosinophilia and elevated serum IgM. The exact etiology remains unclear. Currently, the only treatment strategy is the administration of high dose of steroids during the acute phases. We report the case of a 37-year-old man suffering from GS with recurrent episodes of angioedema, fever, hypereosinophilia [6000/mmc (45%)] and high eosinophil cationic protein (ECP) (>200 mcg/l), treated with oral steroids during the acute phase (prednisone 50-75 mg/day), the dose of maintenance being 25 mg/day. No monoclonal components were identified and genetic tests exclude mutations including Bcr/Abl, JAK2 V617F, c-KIT D816V and FIP1L1-PDGFRA. Using Luminex technology, we observed higher serum levels of IL-5, CCL2 and CCL11 during the acute exacerbations in comparison to the clinical remission phases though CCL11 did not achieve statistical significance. The flow-cytometric analysis identified a CD3+CD8- lymphocyte population with high frequency of IL-4, IL-5, and IL-13 producing cells. No clinical benefit was observed after therapeutic strategies with imatinib, interferon-α, cyclosporine-A and azathioprine. Due to high IL-5 serum levels, an intravenous treatment with anti-IL-5 monoclonal antibody mepolizumab (750 mg every 4 weeks) was started. A reduction in the rate of exacerbation phases/year (10±3 vs 2±1; p<0.005), in the eosinophils count both in percentage (28.8±12.8 vs 9.8±3.9; p<0.001) and absolute value (2737±1946 vs 782±333; p<0.001) were observed as well as the ECP serum levels (132.7±62.7 vs 21±14.2 mcg/l; p<0.05). The daily dose of prednisone was significantly reduced (25 vs 7,5 mg). Any adverse effects were recorded. To our knowledge, this case is the first report of the disease successfully treated with mepolizumab, and it could represent a novel therapeutic strategy in GS.